Psychosocial Response to New-Onset Diabetes as a Long-Term Effect of Allogeneic Hematopoietic Stem Cell Transplantation. (October 2017) - Olausson, Jill M.; Clark, Lauren; Morse, Janice M.; Hammer, Marilyn; Allen, Nancy; Grant, Marcia
Currently, little information is available to guide health care practitioners on how to facilitate positive outcomes in individuals who develop new-onset diabetes after allogeneic hematopoietic stem cell transplantation (allo HSCT) for treatment of hematological cancers. Results from this constructivist grounded theory study provide a theoretical framework explaining the psychosocial process of change that middle-age and older adults experience when developing new-onset diabetes in this context. Two predominant factors influenced this change: treatment burden and perception of diabetes. Key findings were that participants with ongoing complications, primarily graft-versus-host disease, experienced a high degree of treatment-related burden and unclear perceptions of diabetes when compared with those with no or few post-allo-HSCT complications. These factors limited their capacity to positively respond to and self-manage their condition. Implications for practice are to thoroughly consider these two factors when developing patient-centered interventions for middle-age and older adults with new-onset diabetes after allo HSCT.